Penerapan Metode Analytical Hierarchy Process dalam Pemilihan Pemasok di Perusahaan Manufaktur - Khoirunnisa, Nanda; Hidayat, Agung Prayudha (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2026)
This study aims to determine the best silica sand supplier at PT GIP using the Analytical Hierarchy Process (AHP) method. PT GIP does not yet have a structured supplier selection method, resulting in mismatches in the quality and quantity of raw materials. AHP is used to systematically compare alternative suppliers based on certain criteria. Data was collected through questionnaires distributed to three related departments, namely purchasing, logistics and quality control, each represented by two respondents. The weights of criteria and alternatives are determined using the geometric mean method, then the aggregate value is calculated to select the supplier with the highest score. PT GIP has two silica sand suppliers, namely SPI and PAP. AHP calculations are carried out using the Super Decision application to ensure objective analysis. The results show that the best supplier is SPI with an aggregate value of 0.513. This method helps PT GIP select suppliers more accurately and efficiently, so that the quality of the raw materials received can be more guaranteed.